Conditioned medium from BV2 microglial cells having polyleucine specifically alters startle response in mice - Ryuji Owada; Yohei Kakuta; Kosuke Yoshida; Shinichi Mitsui; Kazuhiro Nakamura (Scientific Reports, 2022)
Abstract Repeat-associated non-AUG translation (RAN translation) is observed in transcripts that are causative for polyglutamine (polyQ) diseases and generates proteins with mono amino acid tracts such as polyalanine (polyA), polyleucine (polyL) and polyserine (polyS) in neurons, astrocytes and microglia. We have previously shown that microglia with aggregated polyQ led to defective differentiation and degeneration of neuron-like cells. However, it has not been determined whether only microglia containing a specific RAN product, but not other RAN products, is harmful in vitro and in vivo. Here we show that polyL-incorporating microglia specifically led to altered startle response in mice. Aggregated polyA, polyS and polyL induced aberrant differentiation of microglia-like BV2 cells. Differentiated PC12 cells treated with conditioned medium (CM) of polyS- and polyL- but not polyA-incorporating microglia-like BV2 cells showed retraction of neurites and loss of branch of neurites. Injection of the polyL-CM, but not polyA-CM and polyS-CM, into the lateral ventricle lowered startle response in mice. Consistently, polyL induced the highest expression of CD68 in BV2 cells. The lowered startle response was replicated in mice given the polyL-CM in the caudal pontine reticular nucleus (PnC), the key region of startle response. Thus, endogenous RAN proteins having polyL derived from polyQ diseases-causative genes in microglia might specifically impair startle response.